The prognostic significance of incomplete revascularization and untreated coronary anatomy following percutaneous coronary intervention: An analysis of 6, 755 patients with multivessel disease. Issue 7 (30th September 2017) - Iqbal, M. Bilal; Smith, Robert D.; Lane, Rebecca; Patel, Niket; Mattar, Wala; Kabir, Tito; Panoulas, Vasileios; Mason, Mark; Dalby, Miles C.; Grocott‐Mason, Richard; Ilsley, Charles D.; ,
Abstract: Background: More than half of the patients undergoing percutaneous coronary intervention (PCI) have multivessel disease. Whether complete revascularization impacts long‐term mortality or whether selected patients or those with specific coronary anatomy benefit from complete revascularization is unclear. Methods: A total of 14, 452 patients underwent PCI between 2004 and 2015 at Harefield Hospital, UK. Of these, 7, 076 patients had multivessel disease. We excluded 321 patients with left main‐stem stenosis ≥50%, with 6, 755 patients included in the analysis (936 patients had complete revascularization). Results: The unadjusted 3‐year mortality rates were lower with complete revascularization (10.8% vs 13.1%, P  = 0.047). However, multivariable‐adjusted analyses indicated that complete revascularization was not independently associated with mortality (HR = 1.01, 95% CI: 0.78–1.31, P  = 0.939). These findings were unchanged when addressing measured confounding using propensity‐matched analyses (HR = 1.16, 95% CI: 0.81–1.65, P  = 0.417) and inverse probability treatment weighted analyses (HR = 1.01, 95% CI: 0.77–1.33, P  = 0.950); and unmeasured confounding using instrumental variable analyses (Δ = 0.9%, 95% CI: −2.5%, 4.3%, P  = 0.958). There was no association with mortality and untreated LAD disease (HR = 0.92, 95% CI: 0.72–1.17, P  = 0.482) and LCx disease (HR = 0.90, 95% CI: 0.74–1.10, P  = 0.999). However, untreated proximal LAD disease (HR = 1.23, 95% CI: 1.06–1.51, P  = 0.045) and RCA disease (HR = 1.36, 95% CI: 1.08–1.65, P  = 0.007) was associated with increased mortality, particularly in patients with ST‐elevation acute coronary syndrome (STEACS). Conclusions: In this study of unselected patients undergoing PCI, complete revascularization did not confer a mortality benefit. However, the presence of untreated proximal LAD and RCA disease was prognostic in patients with STEACS. Thus, complete revascularization may be considered in select patient groups with anatomical subsets of coronary disease.